2018
DOI: 10.2478/raon-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of papillary thyroid cancer in subacute thyroiditis patients may be higher than it is presumed: retrospective analysis of 137 patients

Abstract: BackgroundThe association of subacute thyroiditis (SAT) and papillary thyroid carcinoma is a rare finding. In this study, we aimed to investigate the prevalence of differentiated thyroid cancer in a cohort of patients followed with the diagnosis of SAT.Patients and methodsWe retrospectively screened medical records of Endocrinology and Metabolism outpatient clinic in the past 20 years for patients with SAT. Patients with nodules and suspicious ultrasonography findings who underwent fine needle aspiration biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…US is mandatory for SAT diagnosis, FNAB recommended in all doubtful cases [ 64 ] 2. Possible co-presence of DTC – tumours not visible in US due to SAT inflammatory lesions [ 76 , 77 ] 2. US monitoring of SAT patients is required …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US is mandatory for SAT diagnosis, FNAB recommended in all doubtful cases [ 64 ] 2. Possible co-presence of DTC – tumours not visible in US due to SAT inflammatory lesions [ 76 , 77 ] 2. US monitoring of SAT patients is required …”
Section: Discussionmentioning
confidence: 99%
“…The authors underlined that SAT can significantly obscure coexisting PTC when inflammatory hypoechoic regions are present [ 76 ]. Gül et al confirmed the diagnosis of PTC in even higher percentage of SAT patients, reaching 4.4% [ 77 ]. Thus, US re-examination after resolution of SAT-related thyroid lesions should always be performed.…”
Section: The Most Important Diagnostic Problemsmentioning
confidence: 99%
“…Endocrine-Related Cancer in older female and the tumors' size occurred in subacute thyroiditis varies from 0.05 cm to 1.2 cm (Gul et al 2018). The prevalence of PTC occurring in subacute thyroiditis is 4.4% regarding a study with 137 patients, which may be much higher than previous finding of 0.43% (5/1152) (Nishihara et al 2008, Gul et al 2018.…”
Section: :7mentioning
confidence: 66%
“…Swelling with pain in the thyroid gland are the clinical finding in patients of subacute thyroiditis associated with DTC. Elevated C-reactive protein, erythrocyte sedimentation rate, FT 4 , and decreased TSH are commonly found (Nishihara et al 2008, Gul et al 2018. Not or poorly visualization thyroid in thyroid scan, as well as low RAIU are helpful to confirm the diagnosis of subacute thyroiditis (Fatourechi et al 2003).…”
Section: :7mentioning
confidence: 99%
“…There are different types of noncancer thyroid diseases, all of which have been adequately studied as risk factors of thyroid cancer. In their observational study, Nurdan et al demonstrated a higher prevalence of differentiated thyroid cancer in patients with subacute thyroiditis [20]. Chen et al revealed the risk of thyroid cancer in a population with Grave's disease in a nationwide cohort study [21].…”
Section: Discussionmentioning
confidence: 99%